2022
DOI: 10.3389/fnagi.2022.881890
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Model for Alzheimer’s Disease Based on Blood Levels of Autophagy-Related Genes

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease. The major problems that exist in the diagnosis of AD include the costly examinations and the high-invasive sampling tissue. Therefore, it would be advantageous to develop blood biomarkers. Because AD’s pathological process is considered tightly related to autophagy; thus, a diagnostic model for AD based on ATGs may have more predictive accuracy than other models. We obtained GSE63060 dataset from the GEO database, ATGs from the HADb and screened 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Genes with decreased expression in astrocytes in 3xTg-AD mice exposed to alcohol versus WT controls but not in 3xTg-AD mice or WT mice exposed to alcohol versus WT controls included the following: the WD repeat-containing protein Wdr17, abundantly expressed in astrocytes and associated with macular degeneration ( Stöhr et al, 2002 ); Smim4, which may be involved in mitochondrial toxicity ( Dennerlein et al, 2021 ); and autophagy-related 16 like 2 (Atg16l2), a proposed peripheral marker of AD ( Qin et al, 2022 ) that has been shown to be a negative regulator of the NOD (nucleotide-binding oligomerization domain)-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome ( Wang et al, 2022 ) and thus may contribute to neuroinflammation ( Fig. 4 B , Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genes with decreased expression in astrocytes in 3xTg-AD mice exposed to alcohol versus WT controls but not in 3xTg-AD mice or WT mice exposed to alcohol versus WT controls included the following: the WD repeat-containing protein Wdr17, abundantly expressed in astrocytes and associated with macular degeneration ( Stöhr et al, 2002 ); Smim4, which may be involved in mitochondrial toxicity ( Dennerlein et al, 2021 ); and autophagy-related 16 like 2 (Atg16l2), a proposed peripheral marker of AD ( Qin et al, 2022 ) that has been shown to be a negative regulator of the NOD (nucleotide-binding oligomerization domain)-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome ( Wang et al, 2022 ) and thus may contribute to neuroinflammation ( Fig. 4 B , Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, machine learning models based on demographic and imaging indicators have been increasingly used to predict disease prevalence. Studies have shown that a multifactor analysis, which considers the relationships between variables, has lower error rates and more reliable results than a single-factor analysis ( 39 ). In this study, we assessed and compared the predictive performance of four specifically chosen machine learning classifiers (RF, SVM, GLM, and XGB) based on cluster-specific GLM expression profiles and established a GLM-based predictive model that demonstrated the highest predictive capability (AUC = 0.989).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, machine learning models based on demographic and imaging metrics have been increasingly used to predict disease prevalence. Some studies confirmed that multivariate analysis takes into account the relationship between variables and therefore has a lower error rate and more reliable results than single-factor analysis (50,51). Since TB is an infectious disease, there is an urgent need for accurate models to predict the prevalence of TB.…”
Section: Discussionmentioning
confidence: 99%